Immunoinformatics design of multivalent epitope vaccine against monkeypox virus and its variants using membrane-bound, enveloped, and extracellular proteins as targets - Waqas, Muhammad; Aziz, Shahkaar; Liò, Pietro; Khan, Yumna; Ali, Amjad; Iqbal, Aqib; Khan, Faizullah; Almajhdi, Fahad Nasser (Frontiers in Immunology, 2023)
The current monkeypox (MPX) outbreak, caused by the monkeypox virus (MPXV), has turned into a global concern, with over 59,000 infection cases and 23 deaths worldwide. The reverse vaccinology technique has led to the development of multivalent epitope-based vaccines with prominent immunological profiles and minimal chance of triggering autoimmune and harmful responses. Herein, we exploited a robust immunoinformatics approach, targeting membrane-bound, enveloped, and extracellular proteins of MPXV to formulate a chimeric antigen. Such a strategy could similarly be applied for identifying immunodominant epitopes and designing multi-epitope vaccine ensembles in other pathogens responsible for chronic pathologies that are difficult to intervene against. Firstly, a reverse vaccinology pipeline was used to select 11 potential vaccine candidates, which yielded 21 immunodominant epitopes (six B-cell, eight cytotoxic T-lymphocyte, and seven helper T-lymphocyte). The selected epitopes were fused with suitable linkers, an adjuvant (Resuscitation-promoting factor), PADRE sequence (13 aa), and HIV TAT sequence (11 aa) to formulate a multivalent epitope vaccine that can promote cross-protection among the MPXV strains. Most finalized epitopes have 70%–100% sequence similarity with the experimentally validated immune epitopes of the vaccinia virus, which can be helpful in the speedy progression of vaccine design. The chimeric vaccine was predicted non-allergen, antigenic, soluble, with suitable physicochemical features, and showed a wide global population coverage (93.62%). Lastly, molecular docking and molecular dynamics simulation computed stable and energetically favourable interaction between the putative antigen and Toll-like receptor 4 (TLR4). Our results show that the multi-epitope vaccine might elicit cellular and humoral immune responses and could be a potential vaccine candidate against the MPXV infection. Further experimental testing of the proposed vaccine is warranted to validate its safety and efficacy profile.